2001
DOI: 10.1007/s003300000814
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between high-grade glioma and metastatic brain tumor using single-voxel proton MR spectroscopy

Abstract: The purpose of this study was to clarify the efficacy of single-voxel proton magnetic resonance spectroscopy (MRS) in differentiating high-grade glioma from metastasis. Thirty-one high-grade gliomas (11 anaplastic gliomas and 20 glioblastomas) and 25 metastases were studied. Proton MRS was performed using point-resolved spectroscopy with echo times (TEs) of both 136 and 30 ms. The peaks for lipid were evaluated at short TE, and those for N-acetyl-aspartate (NAA), creatine (Cr), and choline-containing compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 21 publications
3
108
0
7
Order By: Relevance
“…Burtscher et al (157) showed that HGGs could be differentiated from metastases by the presence of abnormal spectra in the normal-appearing brain tissue adjacent to the lesion. Ishimaru et al (74) showed that the absence of intratumoral Cr peak was suggestive of metastases, since 21 of 25 metastases in this study had no definitive Cr peak. In addition, the authors noticed that the absence of Lip signal at a TE of 30 ms could exclude the diagnosis of metastasis.…”
Section: Mrsi: Metastatic Neoplasm Versus High-grade Glioma (Paper Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Burtscher et al (157) showed that HGGs could be differentiated from metastases by the presence of abnormal spectra in the normal-appearing brain tissue adjacent to the lesion. Ishimaru et al (74) showed that the absence of intratumoral Cr peak was suggestive of metastases, since 21 of 25 metastases in this study had no definitive Cr peak. In addition, the authors noticed that the absence of Lip signal at a TE of 30 ms could exclude the diagnosis of metastasis.…”
Section: Mrsi: Metastatic Neoplasm Versus High-grade Glioma (Paper Ii)mentioning
confidence: 99%
“…The intratumoral MRS is also not able to reliably differentiate between the metastases and glioma (23). Ishmaru et al (74) showed that the absence of intratumoral Cr peak was suggestive of metastasis. In addition, the authors noticed that the absence of Lip signal of a TE of 30 ms could exclude the diagnosis of metastases.…”
Section: Metastatic Neoplasmsmentioning
confidence: 99%
“…The institutional review board of the performing hospital approved this study, and written informed consent was obtained from the legal guardians of pediatric on the basis of MR spectroscopy findings has been difficult because of excessive magnetic susceptibility perturbations and low spatial resolution (24)(25)(26). Because of the technical challenges and inadequate sensitivity or specificity of the use of MR imaging for distinguishing low-from high-grade pediatric brain tumors, invasive tissue biopsy remains the reference standard for tumor grading.…”
Section: Patientsmentioning
confidence: 99%
“…However, the distinction between metastasis and glioblastomas is marginally higher for long TE than it is for short TE spectra. Ishimaru et al (2001) found that glioblastomas are better resolved from metastases in long TE MRS than in short TE due to overlapping peaks and the dynamic range of the detector being dominated by lipids, diminishing the sensitivity to choline and creatine. This subtle difference suggests that long TE MRS might prove a better option to explore this task in the future with bigger samples.…”
Section: Discussionmentioning
confidence: 99%
“…Few in vitro studies were performed (Faria et al, 2011;Gray et al, 1998). The application of long or short echo-time (TE) spectroscopy has also been reported, as the choice of echo time affects the apparent concentration of every metabolite taking into account its transversal relaxation time (Majós et al, 2004) and also considerations about the dynamic range of the detectors (Ishimaru et al, 2001). In Figure 1, the median and interquartile range of example spectra are shown, highlighting the differences between spectral profiles between two echo times and also between two tissue types, brain abscesses and anaplastic astrocytomas, in both echo times.…”
Section: Introductionmentioning
confidence: 99%